Efeito da prática do futebol no desempenho em agilidade, velocidade e coordenação de meninos na categoria dentinho ou sub 11 (10 e 11 anos de idade) - Buzolin Neto, Octávio [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
In Brazil, the practice of Soccer is encouraged very early. It is common remark that parents enroll their sons into soccer schools, promoting the involvement of these children in formal practice. However, there are not many studies that assess the effects of this practice in the physical capacities of children. Thus, the question that guides this study is: children who practice soccer systematically present better development of physical, especially agility, coordination and speed? The objective of this study was to compare the performance in velocity tests, agility and coordination of boys of 10 and 11 years, category dentinho or Sub-11, practitioners of soccer in schools and non practicing. The study included male children, born in 1997 and 1998, formed two groups: group of practitioners of soccer and group of non practicing. To belong to the group of practitioners, the child was regularly engaged for at least 1 year, with 1 hour daily and 2 to 3 times per week. The participants of the group of non practicing were not involved in regular practice of soccer and were paired in weight and stature with participants of the group of practitioners of soccer. Each participant was individually assessed in neutral environment and without foreign interference. For the assessment of the agility, was utilized the (shuttle run) test. The race test 30 meters stopped was employed for the assessment of the speed. The test of fiddling between the cones was employed to measure the coordination. The time spent to perform 1 attempt to each test was used for the comparison between groups. These data were treated, initially, by descriptive statistics (mean and standard deviation) and, subsequently, were compared by means of Anova, for independent samples. The significance level was maintained at 5%. Through analysis of the results the conclusion is that the regular practice ...(Complete abstract click electronic access below)

No Brasil, a prática do Futebol é incentivada desde muito cedo. É comum observar que os pais matriculam seus filhos homens em escolinhas de Futebol, promovendo o engajamento destas crianças na prática formal. Entretanto, não são encontrados muitos estudos que avaliam os efeitos desta prática nas capacidades físicas de crianças. Assim, a questão que norteia este estudo é: crianças que praticam Futebol sistematicamente apresentam melhor desenvolvimento das capacidades físicas, especialmente agilidade, coordenação e velocidade?O objetivo do estudo foi comparar o desempenho em testes de velocidade, agilidade e coordenação de meninos de 10 e 11 anos, categoria dentinho ou Sub-11, praticantes de futebol em escolinhas e não praticantes. Participaram deste estudo crianças do gênero masculino, nascidos em 1997 e 1998, que formaram dois grupos: grupo de praticantes de futebol e grupo de não praticantes. Para integrar o grupo de praticantes, o menino estava regularmente praticando há pelo menos 1 ano, com 1 hora diária e de 2 a 3 vezes por semana. Os participantes do grupo de não praticantes não estavam envolvidos na prática regular do futebol e foram pareados em peso e estatura com os participantes do grupo de praticantes de futebol. Cada participante foi individualmente avaliado em ambiente neutro e sem interferência externa. Para a avaliação da agilidade, foi utilizado o teste de “corrida de vai e vem” (shuttle run). O teste de corrida de 30m parado foi empregado para a avaliação da velocidade. O teste de driblar entre os cones foi empregado para mensurar a coordenação. O tempo gasto para realizar 1 tentativa de cada teste foi utilizado para a comparação entre os grupos. Estes dados foram tratados, inicialmente, por estatística descritiva (média e desvio padrão) e, posteriormente, foram...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Futebol; Futebol - Treinamento tecnico; Desempenho; Capacidade física; Soccer